Urine Albumin Creatinine Ratio Among Diabetic Retinopathy Patient With And Without Diabetic Macular Edema In Moh. Hoesin Hospital Palembang - Rina Astuti; AK Ansyori; Ramzi Amin (International Journal of Retina, 2018)
Introduction: Diabetic Macular Edema is a diffuse thickening in macula which can be found in various severity of Diabetic Retinopathy. There are issue about relationship between Diabetic Macular Edema and albuminuria caused by chronic renal failure. The aim of this study is to know and compare urine albumin creatinine ratio among Diabetic Retinopathy patients with and without Diabetic Macular Edema in Moh. Hoesin Hospital. Methods: Cross sectional study with 25 sample was conducted. Diabetic Retinopathy and Diabetic Macular Edema was classified base on Early Treatment Of Diabetic Retinopathy Study (ETDRS) criteria. T-test, odd ratio and multiple logistic regretion analysis was used to analysed sociodemography characteristic (age and gender), clinical characteristic (duration of DM, hipertension, treatment, body mass indeks and antioksidan consumption), ophtalmology characteristic (visus, anterior segment anomaly and posterior segment/ severity of Diabetic Retinopathy), laboratory characteristic (HbA1c, ureum, creatinine, urine albumin creatinine ratio, and lipid profile). Result: Urine albumin creatinine ratio mean (2146.77 ± 3796.19) in Diabetic Macular Edema and (49.0 ± 45.35) in non-Diabetic Macular Edema; cutoff point 62.00 mg/dL. Odd ratio adjusted for urine albumin creatinine ratio = 18,8. In this research, risk factors which has significantly were urine albumin creatinine ratio (p=0.047) and High-Density Lipoprotein/HDL (p=0.028) with odd ratio 8.571 and 6.67 respectively. Urine albumin creatinine ratio showed significantly high Mann whitney analysis 0.02 (p<0.005). Conclusion: Urine albumin creatinine ratio in Diabetic Retinopathy with Diabetic Macular Edema was higher than without Diabetic Macular Edema. Urine albumin creatinine ratio and High Density Lipoprotein (HDL) are the two important risk factors associated with Diabetic Macular Edema.